Performance measurement of mosques based on Maqasid Alsyariah in Malaysia: governance of resources, processes and outputs / Muhd Fauzi Abd. Rahman - Abd. Rahman, Muhd Fauzi (Institute of Graduate Studies, UiTM, 2018)
The main objective of this study is to examine factors influencing the performance of mosques in Malaysia. As existing frameworks measuring mosque performance is lacking for comparison, this research is limited to the performance measurement frameworks based on for-profit and nonprofit organisations. This study also fills the void by investigating the variables affecting the performance of mosques, as remarkably unique entities. In essence, it seeks to investigate the relationship between the four main variables of performance measurement comprising resources, processes, outputs and outcomes. The fifth variable included in this performance measurement framework is governance, which was tested for its influence on resources and outputs respectively. While variables such as the resources, processes and outputs of mosques can be hypothesized, mosques also have many Syariah objectives as non-profit organisations such as preserving faith, preserving intellect and public interest. These objectives are used in this study as proxy measures of outcomes in the form of the Maqasid Syariah Index. Hence, outcome as a construct in this study is replaced by Maqasid Syariah Index. The survey was conducted throughout Malaysia, including Sabah and Sarawak. Given the population size and the vast geographical area to be covered, self-administered questionnaires survey by mail was used as the main method of data collection…